2021
DOI: 10.1002/adma.202007977
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomaterials: A Rational Deployment of Forces and Geometries in Programming Functional Materials

Abstract: finite element analysis (FEA). Reproduced with permission. [227] Copyright 2013, Springer Nature. d) Optical images of a stretchable single-crystal Si p-n diode with wavy microstructures on a PDMS substrate at −11% (top), 0% (middle), and 11% (bottom) applied strains. Reproduced with permission. [228] Copyright 2006, AAAS. e) The impact of microstructural topography on the electrical output of the TENGs device. Reproduced with permission. [246] Copyright 2012, American Chemical Society. f) Stretchable batterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 310 publications
(400 reference statements)
0
30
0
Order By: Relevance
“…About active MMs, several recent reviews gave very elaborate discussions from different perspectives. [14][15][16] Cai et al proposed a brand-new concept of "mechanomaterials" to define the programming of advanced functional materials by leveraging the force-geometry-property relationships at multiple scales. [14] Qi et al made a deep and systematic summary of active MMs, [15] elucidating their underlying construction principles, classifications, and applications.…”
Section: Flexible Active Metamaterials Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…About active MMs, several recent reviews gave very elaborate discussions from different perspectives. [14][15][16] Cai et al proposed a brand-new concept of "mechanomaterials" to define the programming of advanced functional materials by leveraging the force-geometry-property relationships at multiple scales. [14] Qi et al made a deep and systematic summary of active MMs, [15] elucidating their underlying construction principles, classifications, and applications.…”
Section: Flexible Active Metamaterials Electronicsmentioning
confidence: 99%
“…properties that are unavailable in natural or chemically synthesized materials, have emerged as a revolutionary frontier of physics, chemistry, material science, and engineering. [13][14][15][16] The most salient trait of metamaterials lies in the artificial creation, namely the collective properties root in engineering structures (shape, geometry, and arrangement) of the unit cells rather than the intrinsic properties of the constituents. Therefore, metamaterials open a brand-new direction to design the capability of materials at will.…”
mentioning
confidence: 99%
“…These results suggest the process "retrained" the cardiomyocytes to become more sensitive to subthreshold stimuli, possibility via changes in resting in biological tissues, numerous biomimetic systems and mechano-guided designs take advantage of the reorganization capabilities of nanostructures to enable mechanical training. [16][17][18][19]70 With repeated prestretching, Lin et al found that the randomly oriented nanofibers and nanocrystalline domains of a poly(vinyl alcohol) hydrogel gradually aligned toward the direction of applied stress. The mechanical training produced muscle-like properties including a low Young's modulus, a high fatigue threshold, and high strength.…”
Section: Current Progress Nanomaterials Systems For Biointerface Trai...mentioning
confidence: 99%
“…Inspired by structural organization that enables mechanical adaptation in biological tissues, numerous biomimetic systems and mechano-guided designs take advantage of the reorganization capabilities of nanostructures to enable mechanical training. [16][17][18][19]70 With repeated prestretching, Lin et al found that the randomly oriented nanofibers and nanocrystalline domains of a poly(vinyl alcohol) hydrogel gradually aligned toward the direction of applied stress. The mechanical training produced muscle-like properties including a low Young's modulus, a high fatigue threshold, and high strength.…”
Section: Current Progress Nanomaterials Systems For Biointerface Trai...mentioning
confidence: 99%
“…Shape morphing, [1][2][3][4][5][6][7][8] utilizing the topological or space-time properties [9][10][11] and the ability to control mechanical properties [12] of functional materials [13][14][15][16][17][18][19][20][21][22][23] remain some of the main challenges in materials science. At the same time, the possibility of constructing materials possessing such properties is in high demand as it may lead to the design of structures superior to currently known biomedical and other devices used in various industries.…”
Section: Introductionmentioning
confidence: 99%